Identifying facilitators and barriers to culturally responsive communication for racial, ethnic, sexual, and gender minoritized patients when screened for COVID-19 vaccinations: A scoping review protocol. - Nikhil Kalita; Patrick G Corr; Maranda C Ward; Julia Xavier; Paige L McDonald (PLoS ONE)
Introduction Racial, ethnic, sexual, and gender minoritized groups are considered historically excluded groups and have been disproportionately affected by the coronavirus disease 2019 (COVID-19) pandemic. The influence of social determinants of health (SDOH), including access to screening and treatment, and other systemic and structural factors are largely responsible for these disparities. Primary care practitioner (PCP) competence in culturally responsive screening practices will be critical to reducing the impact of systemic and structural factors serving as barriers to screening and treatment. Correspondingly, improving the capacity of PCPs to communicate with patients in a culturally responsive manner may influence improved screening and treatment outcomes for minoritized groups related to COVID-19. This scoping literature review aims to determine the current breadth of literature on culturally responsive communication (CRC) in regard to COVID-19 vaccination screening for historically excluded, or minoritized groups. Results from this review will inform the development of a training series and social marketing campaign to improve PCPs capacity in CRC. This manuscript provides details on our study protocol. Objectives This scoping literature review aims to analyze existing literature on culturally responsive COVID-19 vaccinations between PCPs and patients in the U.S., specifically for racial, ethnic, sexual, and gender minoritized groups. Results of this scoping review will inform the development of a training series and social marketing campaign to improve capacity of PCPs in this area. Additionally, the review will inform recommendations for future research. Materials and methods This scoping review will be performed following the framework of Arksey and O'Malley and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR). Relevant studies between the years 2019-2022 were identified using a rigorous search strategy across four databases: MEDLINE (via PubMed), Scopus, Cochrane (CENTRAL; via Wiley), and CINAHL (via EBSCO), using Boolean and Medical Subject Headings (MeSH) search terms. Studies will be uploaded to the data extraction tool, Covidence, to remove duplicates and perform a title/abstract screening, followed by a full-text screening. Results The data extraction and analysis phases of the scoping review are in progress. Data will be analyzed for themes related to culturally responsive COVID-19 screening practices in clinical encounters with the identified study populations. Results will be reported by theme and align to PRISMA-ScR guidelines. Discussion To our knowledge, this is the first study to use scoping methods to investigate the barriers and facilitators to CRC of COVID-19 vaccine screening for historically excluded communities in the U.S. The work and results from this research will be directly utilized for the development of nationally-accessible, continuing medical education materials to teach PCPs about CRC, as well as other materials to influence relevant policy changes within the healthcare landscape.